Mit o przypływach emocji - Powierska, Agnieszka (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2015)
A Myth about a Flush of Emotions The essay’s main subject is Zofia Dąbrowska’s animated etude The Sea. The text indicates connections between a woman and a water element that are deeply rooted in culture. It mentions images of the relation between those two themes in Maria Pawlikowska-Jasnorzewska’s poetry. The author of the essay analyses the poetics of the animation and looks for the features which create the etude’s universal character.